IMPLEMENTASI PROGRAM ADIWIYATA DALAM PEMBENTUKAN KARAKTER PEDULI LINGKUNGAN DI SD MUHAMMADIYAH BODON KOTAGEDE - Endah Riyanti; Ika Maryani (Universitas Ahmad Dahlan, 2019)
ABSTRACT Â This study aims to determine the planning, implementation, and evaluation of the adiwiyata program in shaping the character of caring for the environment and to find out supporting factors and obstacles in the implementation of the adiwiyata program in shaping the character of the care for the environment in SD Muhammadiyah Bodon Kotagede. This type of research is a qualitative descriptive study. Data collection methods are done through interviews, observation, and documentation. Research subjects were the principal, the adiwiyata team, teachers, and students. The validity of the data uses triangulation techniques. Analysis techniques using data collections, data reduction, data presentation and drawing conclusions. The results showed that the implementation of the adiwiyata program in shaping the character of caring for the environment had been integrated in policies that were environmentally friendly and integrated in each subject. The integration was socialized to all school members to create an environmentally friendly school agreement. The supporting factors for the implementation of the adiwiyata program are the beautiful school environment, good cooperation between the schools, adequate budget, and environmentally friendly supporting facilities that support the implementation of the adiwiyata program. Factors inhibiting the implementation of the adiwiyata program include that there are still students who are not yet aware of understanding the concept of being environmentally minded and still lacking land for the process of growing green plants.